Salvage hysterectomy after radiotherapy for cervical cancer: literature review - E. Zh. Shakirova; D. I. Zidikhanov (Опухоли женской репродуктивной системы)
Recurrent cervical cancer is a difficult challenge for gynecological oncologist. In this paper we review papers concerning incidence and surgical treatment of pelvic recurrences. A point of interest is studies evaluating completion surgery after radiotherapy/chemoradiotherapy. Surgery after definitive radiotherapy is associated with high morbidity and should be performed only in patients with residual tumor. Magnetic resonance imaging in special regimen can be useful in detecting residual disease.